A STUDY OF ADJECTIVES AND THEIR GRAMMATICAL CLASSIFICATIONS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides a thorough overview of adjectives, examining their role in language and the variety of types used to modify nouns. It begins by defining adjectives and explaining how they help to specify, clarify, and add detail to communication. The main body categorizes adjectives into ten types—descriptive, quantitative, numeral, demonstrative, possessive, interrogative, distributive, proper, compound, and participial—and offers examples for each. The article also covers guidelines for using adjectives in sentences, common pitfalls, and the importance of following the correct order when using multiple adjectives. Concluding sections highlight the role of adjectives in enhancing both spoken and written language, emphasizing their impact on effective communication. This piece is an informative resource for anyone looking to understand the different types of adjectives and improve their use of descriptive language.